2021
DOI: 10.1371/journal.pone.0252606
|View full text |Cite
|
Sign up to set email alerts
|

How trauma related to sex trafficking challenges parenting: Insights from Mexican and Central American survivors in the US

Abstract: Sex trafficking, a form of human trafficking for the purpose of commercial sexual exploitation, with a global prevalence of 4.5 million, has pervasive effects in the mental and physical health of survivors. However, little is known about the experiences and needs of Latinx migrants (the majority of sex trafficking victims in the US) after trafficking, particularly regarding parenting. This QUAL-quant study examines how 14 survivors of sex trafficking (mean age = 30) from Mexico and Central America encounter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
(91 reference statements)
1
1
0
Order By: Relevance
“…In line with previous studies that have identified various service needs for sex trafficking survivors in the United States (Marti Castaner et al, 2021;Macy & Johns, 2011;O'Brien et al, 2019), our study results suggest that the following services would be needed to facilitate survivor recovery and wellbeing: trauma-informed and culturally appropriate services that provide or promote community building, legal assistance, medical care, life skills and employment training, and affordable housing. Our study adds to the existing literature on recovery by identifying specific structural and cultural factors that may need to be addressed when working with Asian women.…”
Section: Discussionsupporting
confidence: 87%
“…In line with previous studies that have identified various service needs for sex trafficking survivors in the United States (Marti Castaner et al, 2021;Macy & Johns, 2011;O'Brien et al, 2019), our study results suggest that the following services would be needed to facilitate survivor recovery and wellbeing: trauma-informed and culturally appropriate services that provide or promote community building, legal assistance, medical care, life skills and employment training, and affordable housing. Our study adds to the existing literature on recovery by identifying specific structural and cultural factors that may need to be addressed when working with Asian women.…”
Section: Discussionsupporting
confidence: 87%
“…Trauma-related impacts on survivors' parenting of their own children can include lack of confidence in parenting abilities, overprotective parenting and avoidance of socialization with other children or adults, and emotional disconnection from children when the caregiver is struggling with chronic stress and/or mental health symptoms (Marti Castaner et al, 2021). Thus, parentchild interventions (e.g., child-parent psychotherapy, parent-child interaction therapy, ARC-based parenting support) or family therapy (e.g., ecologically based family therapy; Murnan et al, 2018) may be important therapeutic modalities for some trafficking survivors.…”
Section: Parenting Supportmentioning
confidence: 99%